Borzni mehurčki in racionalnost špekuliranja - Ferbar, Janez (Naše gospodarstvo, 2009)
In this paper we analyze stock market bubbles and we question their existence. We argue that from the fundamental point of view it is impossible to identify a bubble immediately, but we have to wait a sufficient amount of time to determine whether prices can be justified by future cash flows. We also review other market constraints which show that on a market with rational expectations equilibrium, bubbles should not exist. However, empirical tests show that bubbles do exist and we analyze the behaviour of rational traders, or speculators, who are willing to pay more for an asset that they know they can later resell than they would be willing to pay if they had to keep the asset forever.
Keywords: borze; borzništvo; kalkulacije